Aldyr Schlee e o entrelugar: a questão da fronteira em Uma terra só - Silva, Angelise Fagundes da (2010)
This thesis analyses the short stories from Uma Terra Só (1984) and intends to verify how the motifs related to the bordering space are manifested in this book, considering them from the perspective of making of characters, fictional space, narrative voice and, mainly, of the subject matter. The culture, the language, the literature, the frontier man, the history of both sides of the border line which passes by Rio Grande do Sul state and Uruguay are elements which attest a limit, however, they do not demarcate it in a precise and clear-cut way. On the contrary, such aspects configure this territory as a cultural continuum . This work aims at studying this conception of the physical and social space as well as its evident relation with the aesthetic project which we find in the so called puebleros short stories by Aldyr Schlee.